Investigating the relationship of hydration status on the clinical outcomes of COVID-19 patients - Mahdiye Rezaei; Nader Salari; Amirhossein Naghibzadeh; Mohammad Mohammadi; Alireza Abdi (The Egyptian Journal of Internal Medicine)
Abstract Background Existing evidence suggests that the hydration status of COVID-19 patients may influence clinical indicators and outcomes of the disease. However, there is a lack of research specifically investigating this aspect. Therefore, this study aimed to ascertain the correlation between hydration status and clinical outcomes among COVID-19 patients. Method This descriptive-analytical study included 110 patients hospitalized with COVID-19 at hospitals affiliated with Kermanshah University of Medical Sciences. Hydration status was assessed using the Free Water Deficit tool, mortality was evaluated using the Sequential Organ Failure Assessment (SOFA) tool, and the severity of COVID-19 was determined using the COVID-GRAM Risk Score tool. Data were obtained from clinical examinations and patient records and analyzed using SPSS software, version 24. Results The study included 110 participants with an average age of 58.2 ± 17.9 years. Females constituted 52.3% of the patient population. Additionally, 54% of patients had a history of underlying diseases, and 24.5% exhibited fluid deficiency. Data analysis revealed no statistically significant difference in average hydration scores when considering the main variables of SOFA and COVID-GRAM risk score results, and other variables such as gender, age, underlying diseases, place of residence, tobacco and drug use, respiratory distress, and PCR test results. Furthermore, the Pearson correlation test revealed no significant relationship between the Free Water Deficit tool results and levels of sodium, potassium, urea, creatinine, blood osmolality, total and direct bilirubin, blood lactate, PaO2, FiO2, platelet counts, mean arterial pressure and patient weight. Conclusion The findings of this study did not support the initial research objectives and hypotheses, as no significant relationship was found between hydration status and clinical outcomes in COVID-19 patients. Additionally, 24.5% of the subjects exhibited a fluid deficit. Given that this study is the first to explore this specific aspect, further research is recommended to investigate the hydration status of critically ill patients.